The Role of Teacher and Parent Collaboration in Overcoming Bullying in the Kindergarten Environment - Shafiyah, Sarah; Zainab, Shafura (LIMEEMAS: Jurnal Ilmiah Pendidikan, 2025)
This study aims to analyze the role of teacher-parent collaboration in overcoming bullying in kindergarten settings. The research was conducted at RA Shazia Palembang using a qualitative descriptive approach. Data were collected through observation, interviews, and documentation involving the principal, teachers, and parents. The results showed that bullying in early childhood education still occurs in verbal, physical, and social forms, such as mocking, pushing, taking toys, and excluding peers from play groups. Teachers play an important role in handling bullying through character education, emotional approaches, supervision, and communication with parents. Meanwhile, parents contribute through positive parenting, emotional support, and active communication with the school. The study also found that effective collaboration between teachers and parents can create a safer and more supportive learning environment for children. However, several obstacles were identified, including differences in parenting styles, limited parental time, and a lack of understanding about bullying in early childhood. This research highlights the importance of strengthening school-family partnerships to prevent bullying and support children’s social-emotional development from an early age.